Civil Justice as An Option for Fulfilling Environmental Justice Through The Principles of Ius Curia Novit and Rechtsvinding - Purwendah, Elly Kristiani; Monteiro, Seguito; Rusito, Rusito; Erowati, Eti Mul; Djatmiko, Agoes (JUSTITIA JURNAL HUKUM, 2022)
Civil trials on the principle of ius curia novit and rechtsvinding become a breath of fresh air for justice seekers seeking their laws that fulfill the ideè des rechts (rechtssicherheit: legal certainty, zweckmässigkeit: expediency, and gerechtigkeit: justice). The principle of ius curia novit which means that the judge is considered to know the law becomes a space for judges in making legal discoveries (rechtsvinding). The implementation of laws by judges is not merely a matter of logic and proper use of the mind, but rather the provision of juridical forms rather than basing on juridical experience and judgment rather than basing on abstracts, because the law cannot be complete, only one stage in the process of forming a law that is forced to seek its completeness in the legal practice of the judge. The judge's wiggle room in fulfilling the sense of justice for justice seekers in the environment as the decision No. 374 / Pdt.G / LH / 2019 / PN.Jkt.Pst which granted the lawsuit of the plaintiffs (Advocacy Team of the Capital Movement (Initiative to Clean the Air of the Universe Coalition) based the findings of the judge's law, basing on Decision Number: 36 / KMA / SK / II / 2013 concerning the Enactment of guidelines for handling environmental cases. Keyword: ius curia novit, rechtsvinding, onrectmatigedaad, lawsuit, environment.